Flavonoids, Flavonoid Subclasses and Breast Cancer Risk: A Meta-Analysis of Epidemiologic Studies - Hui, Chang (Public Library of Science, 2013)
BACKGROUND: Studies have suggested the chemopreventive effects of flavonoids on carcinogenesis. Yet numbers of epidemiologic studies assessing dietary flavonoids and breast cancer risk have yielded inconsistent results. The association between flavonoids, flavonoid subclasses (flavonols, flavan-3-ols, etc.) and the risk of breast cancer lacks systematic analysis. OBJECTIVE: We aimed to examine the association between flavonoids, each flavonoid subclass (except isoflavones) and the risk of breast cancer by conducting a meta-analysis. DESIGN: We searched for all relevant studies with a prospective cohort or case-control study design published before July 1(st), 2012, using Cochrane library, MEDLINE, EMBASE and PUBMED. Summary relative risks (RR) were calculated using fixed- or random-effects models. All analyses were performed using STATA version 10.0. RESULTS: Twelve studies were included, involving 9 513 cases and 181 906 controls, six of which were prospective cohort studies, and six were case-control studies. We calculated the summary RRs of breast cancer risk for the highest vs lowest categories of each flavonoid subclass respectively. The risk of breast cancer significantly decreased in women with high intake of flavonols (RR = 0.88, 95% CI 0.80–0.98) and flavones (RR = 0.83, 95% CI: 0.76–0.91) compared with that in those with low intake of flavonols and flavones. However, no significant association of flavan-3-ols (RR = 0.93, 95% CI: 0.84–1.02), flavanones (summary RR = 0.95, 95% CI: 0.88–1.03), anthocyanins (summary RR = 0.97, 95% CI: 0.87–1.08) or total flavonoids (summary RR = 0.98, 95% CI: 0.86–1.12) intake with breast cancer risk was observed. Furthermore, summary RRs of 3 case-control studies stratified by menopausal status suggested flavonols, flavones or flavan-3-ols intake is associated with a significant reduced risk of breast cancer in post-menopausal while not in pre-menopausal women. CONCLUSIONS: The present study suggests the intake of flavonols and flavones, but not other flavonoid subclasses or total flavonoids, is associated with a decreased risk of breast cancer, especially among post-menopausal women.